HUBUNGAN STRATEGI COPING DAN RESILIENSI DENGANKETIDAKJUJURAN AKADEMIK PADA MAHASISWAPREKLINIK FAKULTAS KEDOKTERAN UNIVERSITASPEMBANG8NAN NASIONAL ³9ETERAN´ JAKARTA - Faadhilah Widya Prananda, (2023)
Students as members of the academic community are required to uphold academic integrity, such as honesty, trust, fairness, respect and responsibility. Academic dishonesty is a form of violation of academic integrity that can be influenced by various factors, one of which is self-control which includes coping strategies and resilience. Therefore, coping strategies and resilience are important to overcome problems in higher education. The purpose of this study was to determine the relationship between coping strategies and resilience with academic dishonesty, especially in UPNVJ Medical Faculty preclinical students. This research is an observational analytic study with a cross sectional study. The sample used in this study was UPNVJ Faculty of Medicine students in the 2019, 2020, and 2021 batches of 229 people using a stratified random sampling technique. The statistical test used in this study uses the Chi Square test. From the results of the Chi Square test, the P value between coping strategies and academic dishonesty was 0.552 and the P value between resilience and academic dishonesty was 0.003. So it can be concluded that there is no relationship between coping strategies and academic dishonesty, and there is a relationship between resilience and academic dishonesty.